Analisis Permintaan Karet Alam Indonesia di Pasar Internasional - Happy Dewi Purnomowati; Dwidjono Hadi Darwanto; Sri Widodo; Slamet Hartono (AGRARIS: Journal of Agribusiness and Rural Development Research, 2015)
The development of the natural rubber market in three years was relatively favorable for producers, which was indicated by the relatively high price level. This was due to increasing demand. Of course this will be a good opportunity for Indonesia to export processed rubber and rubber industry in Indonesia to other countries. The purpose of this study was to determine the factors that can affect demand for Indonesia's natural rubber exports in each country's export destinations. The data used was secondary data years 1980-2013 time series derived from IRSG, BPS, FAO, Gapkindo, UN Comtrade, BI, and the World Bank. Methods of analysis using dynamic demand model "Stock Adjustment Principle", Nerlove (1983) and the model of Ordinary Least Square (OLS), Auto Correlation Models and Two Stage Least Square (2SLS) with modifications to several independent variables. The results showed that Indonesia's natural rubber demand in the market of the United States, China, Japan, Singapore, and South Korea is positively influenced by the volume of exports last year, the population of a country, and per capita income of a country. As well as negatively affected by the exchange rate of a country's currency against the US dollar and the implementation of the export quota policy.